Objective Estimates of Physical Activity and Sedentary Time among Young Adults. (2nd January 2017) - Unick, Jessica L.; Lang, Wei; Tate, Deborah F.; Bond, Dale S.; Espeland, Mark A.; Wing, Rena R.
Abstract : Background . This study examines factors associated with physical activity (PA) and sedentary behaviors (SB) in young adults (18–35 years) and compares objective and subjective assessment measures of PA and SB. Methods . 595 young adults (27.7 ± 4.4 years; 25.5 ± 2.6 kg/m 2 ) enrolled in the Study of Novel Approaches to Weight Gain Prevention (SNAP) trial. Hours/day spent in SB (<1.5 METs) and minutes/week spent in bout-related moderate-to-vigorous intensity PA (MVPA; ≥3 METs and ≥10 min) were assessed using self-report and objective measures. Demographic factors associated with SB and MVPA were also explored (i.e., age, gender, BMI, ethnicity, work and relationship status, and number of children). Results . Objective MVPA (263 ± 246 min/wk) was greater than self-report estimates (208 ± 198 min/wk; p < 0.001 ) and differed by 156 ± 198 min/wk at the individual level (i.e., the absolute difference). Females, overweight participants, African Americans, and those with children participated in the least amount of MVPA. Objective estimates of SB (9.1 ± 1.8 hr/day; 64.5% of wear time) were lower than subjective estimates (10.1 ± 3.5 hr/day; p < 0.001 ), differing by 2.6 ± 2.5 hr/day for each participant. Conclusion . Young adults interested in weight gain prevention engage in both high levels of MVPA and SB, with participants self-reporting fewer MVPA minutes and more SB compared to objective estimates. This study is registered at ClinicalTrials.gov (NCT01183689 ).